Culture in the EFL Classroom: Western Instructions and Arab Students in the UAE - Palmer, Bridget M. W. (2013)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Bridget M. W. Palmer entitled, "Culture in the EFL Classroom: Western Instructors and Arab Students in the UAE," December 2013. Thesis advisor is Dr. Ahmad Al-Issa. Available are both hard and soft copies of the thesis.